Pemberian Tepung Bawang Dayak (Eleutherine palmifolia) dalam Pakan terhadap Profil Hematologi Darah Puyuh: The Effect of Feeding of Eleutherine palmifolia Meal in Diet on The Hematological Profile of Quail (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
The study evaluated the effects of feeding Bawang Dayak (Eleutherine palmifolia) meal in the diet on the hematology profile in quails. A total of 160-layer quails (Coturnix-coturnix japonica strain) aged 8 weeks to 14 weeks were assigned on a completely randomized design (CRD) with 4 treatments, 4 replications with 10 quails per replication. The treatments consisted of R1 = diet control, R2 = diet contained 0.1% Bawang Dayak meal, R3 = diet contained 0.2% Bawang Dayak meal, and R4 = diet contained 0.3% Bawang Dayak meal. The variables observed were the hematology profile quail, including erythrocytes, hemoglobin, leukocytes, hematocrit, lymphocytes, heterophils, eosinophils, monocytes, basophils, and the ratio of heterophils to lymphocytes (H/L). Data were analyzed using analysis of variance (ANOVA), and any significant differences were tested using a post hoc Tukey test. The results showed that the usage of Bawang Dayak meal as a phytobiotic in the diet up to 0.3% did not affect quail blood hematology such as erythrocytes, hemoglobin, leukocytes, hematocrit, leukocyte differentiation and the ratio of H/L. The inclusion of 0.2% Bawang Dayak meal resulted in the H/L ratio being within normal conditions, reflecting its function to maintain stress levels of layer quails.  In conclusion, utilization of Bawang Dayak meal in a diet of up to 0.3% does not affect the hematological profile of quail.Key words: bawang dayak, Eleutherine palmifolia, hematology, quail